PENGAMANAN JARINGAN WIRELESS LAN DENGAN PROTOKOL EAP-TTLS DAN OTENTIKASI MSCHAPV2 PADA FAKULTAS ILMU KOMPUTER UPN VETERAN JAKARTA - Kukuh Bagas Permadi (2020)
The use of the WPA protocol has two processes, including authentication and encryption. At the network level with large infrastructure and high network traffic as well as universities, corporate offices or other public places that use wireless LANs, the authentication process is the first process done so that wireless LAN network users can access the internet network. Therefore, it is not only safe but the authentication process can operate quickly. The solution of this research is to implement the IEEE 802.1x EAP Protocol with Extensible Authentication Protocol - Tunneled Transport Layer Security (EAP-TTLS) to create a secure tunnel (security tunnel) in key exchange on a wireless network, as well as with the inner authentication of the Microsoft Challenge Handshake Authentication Protocol. Version 2 (MSCHAPv2). The output produced in this study is to build a security on a centralized wireless network at the Faculty of Computer Science UPN Veteran Jakarta.